CORRELATE OF DESTINATION ACCESSIBILITY, LEISURE TOURISTS’ SATISFACTION AND REVISIT INTENTION IN AKWA-IBOM STATE, SOUTH-SOUTH NIGERIA - ETUK, Joseph Sunday; ANOSIKE, Ugochukwu Miracle (American Journals, 2022)
It has been argued that travelling in Nigeria is travail, and poor access to tourist sites accounts significantly for the dismal tourism performance in some states and regions in Nigeria. Therefore, this study was carried out to empirically ascertain destination accessibility and tourists’ satisfaction in Akwa-Ibom State, South-South Nigeria. To carry out the study, a survey method was adopted whereby primary data were obtained from 306 respondents through the questionnaire method. Descriptive and univariate analysis was done using simple percentages, mean score, standard deviation while the Pearson Product Moment Correlation technique was deployed for hypotheses testing. The analyzed data revealed that destination accessibility was strongly positively correlated with tourists’ satisfaction and revisit intention, but the correlation was insignificant. This implies that tourists were impressed by the accessibility system of Akwa-Ibom, even to the tourists’ sites, however, their total experience at the tourist sites was not satisfactory due to unavailability of adequate modern facilities. The recommended the provision of adequate facilities by the tourist sites’ management for visitors’ fun and relaxation and revisit intention.
Keywords: Destination accessibility, tourists’ satisfaction, revisit intention